Critical review of current understanding of passive façade design in residential buildings - Yilin Lee; Edward Ng (Environmental Research: Infrastructure and Sustainability)
A systematic literature review is an objective method to critically evaluate current understanding in the field of building façades. Due to the topical nature of climate change and its impact on the design and performance of facades, the review will critically evaluate selected studies on their ability to respond to current climate (climate-responsiveness) and future climate changes. The study focuses on residential façades since a lack of research was identified for residential (64 studies) compared to commercial façades (255 studies). The study employs the PRISMA model to identify 105 relevant studies. These were analysed to provide a comprehensive understanding of the current body of literature on residential façades. Common focus domains were grouped into following research clusters: aesthetics, acoustics, structure, sustainability, pathology, thermal comfort, and natural ventilation, energy efficiency and building performance. Two types of research gaps were identified, gaps by climate and building height, and authors’ self-reported gaps. Reported research gaps were grouped into 3 categories: data, methodology and theory. Quantitative building performance has been thoroughly studied. However, the impact of human behaviour, elements of future change, and climate change on building performance present research gaps which require further investigation. Moreover, only 15 studies (14.3%) were conducted for a tropical climate, and only 8 (7.6%) studies investigated high-rise buildings. High-density megacities and high-rise buildings will become more common, and mainly concentrated in tropical and subtropical regions. It is, therefore, important to research how residential façades should be designed for high-rise buildings in hot climates considering future change. The critical evaluation assesses whether and how these studies address climate change and extreme weather. Additionally, socio-economic changes are important. Land scarcity, increasing real estate values, and shrinking family size could lead to smaller flat sizes. Future work may consider the delicate balance between façade ratio, flat size, energy, cost, and comfort.